Perfectionistic concerns, other-oriented perfectionism and marital satisfaction among working women in Jakarta - Maria Clayriza Yovani; Pingkan C.B. Rumondor (Jurnal Ecopsy, 2021)
Nowadays, divorce is increasing in the community every year. In recent years, the wife often litigates for divorce due to marital dissatisfaction. Several aspects influence marital satisfaction one of them is the perfectionism trait beget in every individual, albeit at different levels. Perfectionism trait causes individuals to set high demands on others (other-oriented perfectionism) and themselves (perfectionistic concerns). Diverse cultural and working backgrounds uphold the demand in marriage. Thus, this research examines the correlations of perfectionistic concerns and other-oriented perfectionism with marital satisfaction in early adult working women in Jakarta. This research applied a quantitative approach and obtained the data by distributing questionnaires, adopted from ENRICH Marital Satisfaction (EMS) and Dyadic Perfectionism Scale (DPS) to 73 respondents working in the media and banking. Data were analyzed by using Spearman’s correlation. Both perfectionistic concerns and other-oriented perfectionism are associated with lower marital satisfaction. It implies that perfectionistic concerns drive the wife to be perfect in marriage, thus, burdening her psychologically. Furthermore, the wife also puts high demands on her husband to be perfect and thinks that she deserves that. The marriage is at a stalemate due to a lack of healthy communication in achieving greater marital satisfaction.